(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
In this article effectively teaching English in modern classes is learned. By embracing technology, catering to diverse learning styles, fostering collaboration, using authentic materials, providing continuous feedback, promoting cultural awareness, building strong relationships, and encouraging lifelong learning, we can create a dynamic and engaging learning environment that not only helps students master the English language but also inspires a lifelong love of learning.